2012
DOI: 10.1186/1471-2490-12-14
|View full text |Cite
|
Sign up to set email alerts
|

miR-21 may acts as an oncomir by targeting RECK, a matrix metalloproteinase regulator, in prostate cancer

Abstract: BackgroundPrognosis of prostate cancer (PCa) is based mainly in histological aspects together with PSA serum levels that not always reflect the real aggressive potential of the neoplasia. The micro RNA (miRNA) mir-21 has been shown to regulate invasiveness in cancer through translational repression of the Metaloproteinase (MMP) inhibitor RECK. Our aim is to investigate the levels of expression of RECK and miR-21 in PCa comparing with classical prognostic factors and disease outcome and also test if RECK is a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(90 citation statements)
references
References 23 publications
3
86
0
1
Order By: Relevance
“…MiR-21 is known as an oncomiR, which is over-expressed miRNA in many cancers, and functions to regulate cell proliferation and apoptosis during neoplastic progression in a variety of cancers. 8,9 The decrement of miR-21 and miR-223 after surgery was concordant with previous report in HNSCC.…”
Section: Discussionsupporting
confidence: 80%
“…MiR-21 is known as an oncomiR, which is over-expressed miRNA in many cancers, and functions to regulate cell proliferation and apoptosis during neoplastic progression in a variety of cancers. 8,9 The decrement of miR-21 and miR-223 after surgery was concordant with previous report in HNSCC.…”
Section: Discussionsupporting
confidence: 80%
“…Another invasionrelated gene regulated by miR-21 is RECK, a matrix metalloproteinase inhibitor. Neutralizing miR-21 represses the matrix metalloproteinase levels and reverses the invasive phenotype [62]. Recently, Wang et al [63] found that miR-573 expression was significantly lower in metastatic tissues than matched primary PCa.…”
Section: Role Of Mirnas In Prostate Cancermentioning
confidence: 99%
“…Potential miRNA-binding sites have been predicted in the 39 untranslated region of ADAM17, uPA, and several MMPs (Dalmay and Edwards 2006;Bracken et al 2014), and a growing number of studies have provided functional validation of miRNAmediated regulation of proteases in cancer . It has also been reported that miRNAs contribute to the down-regulation of inhibitors and other protease regulators, which in turn leads to protease activation (Gabriely et al 2008;Reis et al 2012). In future studies, it will be critical to determine whether the other reported mechanisms that alter protease expression in cancer similarly change protein localization and consequently impact pericellular proteolysis.…”
Section: Induction and Regulation Of Pericellular Proteolysis In Cancermentioning
confidence: 99%